Ten Crises : The Political Economy of China$1 (Bs Development (1949-2020)s - Tiejun, Wen (Springer Nature, 2021)
This open access handbook, Ten Crises systematically traces the economic history of China from 1949 to 2020, unravelling the complex domestic and global factors leading to the cyclical crises identified by WEN and his research team, and examining the corresponding counteracting policies and measures by the government to resolve or defer the crises. The book offers profound insights into China$1 (Bs endeavours and predicaments on the path of modernization, and contemplates opportunities and lessons for the forging of alternative trajectories not only for China but also for the global south: to reconstruct rural communities for integrated cooperation and governance, and to revitalize ecological civilization.s
English
Keywords: Economics; Public finance; Economic history; Development economics & emerging economies; Economic theory & philosophy; Macroeconomics; Economy-wide Country Studies; Public Economics; Economic History; Development Economics; Economic Theory/Quantitative Economics/Mathematical Methods; Macroeconomics/Monetary Economics//Financial Economics; Quantitative Economics; Macroeconomics and Monetary Economics; Asia; China; Development; Economics; Growth; History; Industrialization; Macroeconomics; Open Access; Public finance & taxation; Development economics & emerging economies; Economic theory & philosophy; Monetary economics